DeepRD:LSTM-based Siamese network for Android repackaged applications detection - Run WANG; Benxiao TANG; Li’na WANG (Tongxin xuebao)
The state-of-art techniques in Android repackaging detection relied on experts to define features,however,these techniques were not only labor-intensive and time-consuming,but also the features were easily guessed by attackers.Moreover,the feature representation of applications which defined by experts cannot perform well to the common types of repackaging detection,which caused a high false negative rate in the real detection scenario.A deep learning-based repackaged applications detection approach was proposed to learn the program semantic features automatically for addressing the above two issues.Firstly,control and data flow analysis were taken for applications to form a sequence feature representation.Secondly,the sequence features were transformed into vectors based on word embedding model to train a Siamese LSTM network for automatically program feature learning.Finally,repackaged applications were detected based on the similarity measurement of learned program features.Experimental results show that the proposed approach achieves a precision of 95.7% and false negative rate of 6.2% in an open sourced dataset AndroZoo.